Psychometric properties of persian version of the bakas caregiving outcomes scale - Maryam Khoshbakht Pishkhani; Abbas Ebadi; Asghar Dalvandi; Manijeh Dehi Aroogh; Nazila Vosoghi; Kobra Ghorbanzadeh (Wolters Kluwer Medknow Publications, 2022)
Background: Caregivers of stroke patients have many problems due to caring for patients. This study aimed to evaluate the psychometric properties of the Persian Version of the Bakas Caregiving Outcomes Scale (BCOS) in caregivers of stroke patients. Materials and Methods: This methodological study was conducted in 2018 with 191 caregivers of stroke patients. In order to assess the scale validity and reliability, the face, content, internal consistency, stability of the scale, and construct validity (exploratory and confirmatory factor analysis) were done. Results: The scale face and content validity qualitatively were checked and confirmed by caregivers' and experts' opinions. In the reliability, Cronbach's alpha was obtained to be 0.93. The test-retest was conducted on 30 participants and showed good stability after 2 weeks. The Intraclass Correlation Coefficient (ICC) for the total scores was reported to be 0.94. The Kaiser-Meyer-Olkin p value was 0.90, Bartlett's sphericity test was significant (p < 0.001), in the exploratory factor analysis, 2 factors with 14 items were extracted. The confirmatory factor analysis confirmed the appropriate model with 14 items (removal of item 13) with two factors at the expected level. Conclusions: The Persian version of the 14 items of the BCOS indicates satisfactory reliability, and validity in the Iranian caregivers of stroke patients.